Respuesta :

Answer:

the solution of the system is:

x = 1 and y = 2.

Step-by-step explanation:

I suppose that we want to solve the equation:

-6*x + 6*y = 6

6*x + 3*y = 12

To solve this, we first need to isolate one of the variables in one of the equations.

Let's isolate y in the first equation:

6*y = 6 + 6*x

y = (6 + 6*x)/6

y = 6/6 + (6*x)/6

y = 1 + x

Now we can replace this in the other equation:

6*x + 3*(1 + x) = 12

6*x + 3 + 3*x = 12

9*x + 3 = 12

9*x = 12 - 3 = 9

x = 9/9 = 1

Now that we know that x = 1, we can replace this in the equation "y = 1 + x" to find the value of y.

y = 1 + (1)  = 2

Then the solution of the system is:

x = 1 and y = 2.

ACCESS MORE